2002
DOI: 10.1007/s00125-002-0797-6
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of autoimmunity to beta-cell antigens by proteases

Abstract: Aims/hypothesis. Proteases are used in therapy for autoimmune diseases yet the mechanism of their action remains to be determined. We studied the immunological basis of protease therapy in the context of Type I (insulin-dependent) diabetes mellitus. Methods. We studied the effects of proteases (trypsin, papain, chymotrypsin, bromelain) on immune reactivity of a series of autoreactive T-cell clones from prediabetic subjects and patients with a recent onset of Type I diabetes and specific to the autoantigens GAD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
3

Year Published

2002
2002
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 38 publications
0
18
0
3
Order By: Relevance
“…Autoreactive T-cell proliferation was inhibited at pharmacological serum concentrations, whereas non-specific proliferation to phytohaemagglutinin was not affected at these concentrations. Preincubation experiments on T-cells and antigen-presenting cells separately showed that this effect was mediated by APCs, but not T-cells [57].…”
Section: T-cell Assay Standardizationmentioning
confidence: 93%
See 2 more Smart Citations
“…Autoreactive T-cell proliferation was inhibited at pharmacological serum concentrations, whereas non-specific proliferation to phytohaemagglutinin was not affected at these concentrations. Preincubation experiments on T-cells and antigen-presenting cells separately showed that this effect was mediated by APCs, but not T-cells [57].…”
Section: T-cell Assay Standardizationmentioning
confidence: 93%
“…Firstly, autoreactive T-cell clones have been used to identify candidate islet autoantigens that had not previously been characterised by autoantibodies [53,54]. Secondly, autoreactive T-cell clones isolated from newly diagnosed or pre-diabetic patients have been used to design and study potential immunotherapeutic strategies in vitro, such as chimeric soluble ICAM-1 and -3 (important intercellular adhesion molecules required for costimulation of T-cells and extravasation) [55,56], proteases [57], and altered peptide ligands of autoantigenic peptide epitopes [58]. These altered peptide ligands efficiently down-regulate in vitro activation of a 38 kD-specific Th1 clone induced by either its peptide epitope or by native beta cell autoantigen.…”
Section: T-cell Assay Standardizationmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its proteolytic activity, bromelain has been extensively used in therapeutic applications in several animal models (Ahle 1987;Bahde 2007;Bhui et al 2009). A wide range of therapeutic benefits have been attributed to bromelain due to its action as therapeutic target in inflammation, autoimmunity and allergy, as well as the reversible inhibition of platelet aggregation, bronchitis relief, improved recovery after surgical traumas, and enhanced absorption of drugs, particularly of antibiotics (Kelly 1996;Murakawa 2002;Roep 2002;Secor 2009). Enzymatic debridement of necrotic tissues from ulcers, burn wounds and frostbite eschar as well as anti-proliferative and anti-metastatic effects in tumor models have been also studied (Ahle 1987;Napper et al 1994;Bhui et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A wide range of therapeutic benefits have been attributed to bromelain due to its action as therapeutic agent in inflammation, autoimmunity and allergy, as well as the reversible inhibition of platelet aggregation, bronchitis relief, improved recovery after surgical traumas, and enhanced absorption of drugs, particularly antibiotics [7][8][9][10]. Enzymatic debridement of necrotic tissues from ulcers, burn wounds and frostbite eschar, as well as antiproliferative and antimetastatic effects on tumor models have been also presented in Refs.…”
Section: Introductionmentioning
confidence: 99%